Impact of using information and communication technology and renewable energy on health expenditure: A case study from Pakistan. (1st August 2020) - Shahzad, Khuram; Jianqiu, Zeng; Hashim, Muhammad; Nazam, Muhammad; Wang, Lei
Abstract: The objective of this study is to explore the dynamic linkages between health expenditure, economic growth, CO2 emission, information and communication technology and renewable energy consumption in the case of Pakistan. To fulfill the study objective, a variety of econometric methods is employed over the period of 1995–2017. The results indicated the dynamic linkages among under-considered variables. The results established that economic growth and CO2 emission have a positive Impact on health expenditure, while information and communication technology and renewable energy consumption have a negative impact on health expenditure. Moreover, bidirectional Granger causality is confirmed between Health expenditure, economic growth, carbon dioxide emission, and information and communication technology. The unidirectional causality is running from renewable energy consumption to these variables. Short-run causality is running from renewable energy consumption to health expenditure and economic growth. Furthermore, short-run causality is running from information and communication technology to economic growth. Consequently, this study empirically contributed by confirming the critical role of information and communication technology and renewable energy consumption in reducing health expenditure. So, the policymakers should invest in information and communication technology and renewable energy projects to enhance air quality and provide a healthy environment to society. Highlights: This study established that ICT reduces health expenditure and CO2 emission. Renewable energy consumption reduces health expenditure and CO2 emission. CO2 emission and economic growth have a positive impact on health expenditure. Health expenditure, CO2 emission, economic growth, and ICT have two-way causality. Renewable energy causes health expenditure, CO2 emission, economic growth, and ICT.